An unusual case of invasive pleuritis and miliary Mycoplasma pneumonia during check‐point inhibitor therapy. Issue 9 (29th July 2021) - Bird, Daniel; Singh, Maninder
Abstract: A growing body of evidence suggests that check‐point inhibitors not only increase the overall risk of infections, but, due to an altered immune response, may also result in atypical manifestations. We report a case of a 38‐year‐old man with pleuritic chest pain, dyspnoea, fevers and a dry cough receiving combination ipilimumab and nivolumab immunotherapy for metastatic melanoma. Radiological findings demonstrated a diffuse increased fluorodeoxyglucose avidity of the thoracic pleura in addition to a disseminated miliary pattern of pulmonary nodularities. A subsequent bronchoscopy was macroscopically normal with unremarkable washings. In the context of a significantly elevated Mycoplasma serology, a diagnosis of Mycoplasma pneumoniae pneumonia (MPP) was made. The patient was successfully treated with a course of azithromycin and amoxicillin‐clavulanic acid. We suggest an awareness of diffuse pleuritis and a disseminated miliary nodular pattern as atypical manifestations of MPP, potentially attributable to immune modulation in the context of immunotherapy. Abstract : A novel case of disseminated miliary Mycoplasma pneumonia with invasive diffuse pleural involvement is reported. This is an atypical manifestation of a relatively common presentation likely due to altered immunity from concurrent check‐point inhibitor immunotherapy for metastatic melanoma.